Pengaruh Profitabilitas, Ukuran Perusahaan Dan Ukuran Dewan Komisaris Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Chelsya (Jurnal Ekonomi, 2018)
This research aims to determine the factors that influence the level of Corporate Social Responsibility Disclosures by testing the effect of corporate size, profitability, and board of director size on the corporate social responsibility disclosures index. Sample used are manufactur sector companies that listed on Indonesia Stock Exchange. The sources of the data were taken from audited financial reports and annual reports and sustainability report, if any. This research uses quantitative approach with multiple linier regression analysis. The results show that profitability, firms size and board of director size have a positive effect on corporate social responsibility disclosures.